KEPENTINGAN PEMERINTAH INDONESIA MENGELUARKAN KEBIJAKAN PEMBATASAN KUOTA IMPOR TEPUNG GANDUM - Separinta, Aradella; Tjarsono, Idjang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This is research aims to explain the interest of Indonesian government published policy on quota import restriction of wheat flour. The government purpose of this policy is to protect the domestic industry by applying this quota restriction system domestic industry can compete with import products. The countries that applied quota import restriction are Turki, Srilanka and Ukraina. This policy created based on the regulation from minister of commerse republic of Indonesian with number 23/M-DAG/PER/4/2014.The theories used in this research is foreign policy theory the author used merchantilisme approach and nation-state level analyze. Data of this research was obtained from books, journals, articles, official documents and websites that support the hyphotesis.The results of this research shows that there is on economic politic interest in that quota import restriction. This policies made to provide assisteance and profit to the domestic industry, because with this policy the import products are no longer flooded of domestic market and domestic industry can be compete with import products.Keywords: policy on quota import restriction flour, flour protection of trade order